1994
DOI: 10.1063/1.112768
|View full text |Cite
|
Sign up to set email alerts
|

Metallic glass formation in highly undercooled Zr41.2Ti13.8Cu12.5Ni10.0Be22.5 during containerless electrostatic levitation processing

Abstract: Various sample sizes of Zr 41.2 Ti 13.8 Cu 12.5 Ni 10.0 Be 22.5 with masses up to 80 mg were undercooled below T g ͑the glass transition temperature͒ while electrostatically levitated. The final solidification product of the sample was determined by x-ray diffraction to have an amorphous phase. Differential scanning calorimetry was used to confirm the absence of crystallinity in the processes sample. The amorphous phase could be formed only after heating the samples above the melting temperature for extended p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(98 citation statements)
references
References 9 publications
3
94
0
1
Order By: Relevance
“…This diagram reveals a large asymmetry in the crystallization behavior between cooling from the stable melt and heating the amorphous sample. In agreement with previous results 10 we found a critical cooling rate for Vit 1 of about 1 K/s. However, the critical heating rate of approximately 200 K/s is about two orders of magnitude larger.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This diagram reveals a large asymmetry in the crystallization behavior between cooling from the stable melt and heating the amorphous sample. In agreement with previous results 10 we found a critical cooling rate for Vit 1 of about 1 K/s. However, the critical heating rate of approximately 200 K/s is about two orders of magnitude larger.…”
supporting
confidence: 82%
“…The critical cooling rate of Zr 41 Ti 14 Cu 12 Ni 10 Be 23 ͑Vit 1͒, studied in this work, is about 1 K/s. 10 In contrast, crystallization of amorphous Vit 1, previously investigated by differential scanning calorimetry ͑DSC͒ upon heating 11 could not be avoided up to the maximum heating rate of the DSC of 5 K/s and the critical heating rate has not been determined yet. The critical heating rate R h , the counterpart of the critical cooling rate upon heating, is the lowest rate an amorphous sample can be heated through the entire supercooled liquid region without crystallization.…”
mentioning
confidence: 99%
“…Among those BMG systems developed, Cu-Zr-based BMGs are among the most popular amorphous alloys that possess the advantages of low material cost, superior mechanical properties, and good glass-forming ability (GFA) [1][2][3][4][5]. Recent works reported that a Cu-Zr-based Cu 42 Zr 42 Al 8 Ag 8 alloy with large critical dimensions and high fracture strengths can be prepared by copper mold casting [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The sample temperature was measured using an E 2 T pyrometer ͑model 7000ET-1HR͒. Prior to the temperature measurements, the pyrometer was calibrated using the known eutectic temperature of 937 K. Initially, the molten sample was cooled radiatively to a predetermined temperature by blocking the heating source of a xenon arc lamp.…”
mentioning
confidence: 99%
“…By applying the HVHTESL technique to the Zr 41.2 Ti 13.8 Cu 12.5 Ni 10.0 Be 22.5 alloy, for example, the authors found that proper thermal treatment during solification results in the ''self-fluxing'' of the melt, allowing it to successfully undercool down to the glass transition with cooling rates of about 1 K/s. 7 Detailed thermodynamic studies were made to explain the stability of the undercooled liquid. 8 Thermophysical properties, such as specific heat capacity and total hemispherical emissivity, over the whole range of the undercooled liquid have been determined.…”
mentioning
confidence: 99%